Comprehensive rehabilitation of patients with movement disorders with spastic forms of cerebral palsy - O. V. Bugun; A. V. Mashanskaya; A. V. Atalyan; V. I. Mikhnovich; T. A. Belogorova; A. V. Vlasenko; V. R. Minulin; Zh. V. Prokhorova (Acta Biomedica Scientifica, 2021)
Until now, there is no radical method of treating children with cerebral palsy, which allows us to consider scientific research in this direction reasonable and promising.The aim of the research: to study the effect of exercises on the mini-simulator “Kinesioplatform-swing” with biofeedback on the indicators of motor skills in children with spastic cerebral palsy.Materials and methods. We conducted an open, non-randomized, prospective, comparative, controlled study in pairs (each participant in the main group corresponds to a participant in the control group). The study involved 53 patients aged 4–12 years with cerebral palsy: the intervention group (group 1: n = 27 (13 boys, 14 girls)) and the control group (group 2: n = 26 (11 boys, 15 girls)), comparable in terms of gender, age and severity of movement disorders. Characteristics of the medical intervention: group 1 – botulinum toxin type A (BTA, for exercising against the background of relative muscular normotonus) + exercise therapy + exercises on the mini-simulator “Kinesioplatform-swing” with biofeedback (BFB); group 2 – BTA + exercise therapy. Duration of the study: 2019–2020. The difference between groups in terms of motor skills on the day of hospitalization and after completion of the training program (10 sessions each) was determined. Motor skills were assessed according to the GMFM-66/88 (Gross Motor Function Measure) table using the “Scales for measuring global motor functions”.Results. The inclusion of additional exercises on the mini-simulator “Kinesioplatformswing” with biofeedback in the rehabilitation of patients with movement disorders with spastic cerebral palsy (BTA + exercise therapy) in comparison with the control group. However, the question of the long-term effects of such training remains open and requires further study.